PENGARUH IMPREGNASI DENGAN RESIN POLIURETAN PADA PROSES FINISHING PENYAMAKAN KULIT SAPI CRUST DYED UNTUK MENGURANGI LOOSE DEFECT ARTIKEL UPPER SHOES - Arianda Kusuma Widuri; Elis Nurbalia; Swatika Juhana (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2018)
Finishing action is a finishing technique for crust dyed leather that has been sanded in the surface and finished to form artificial tattoo. Impregnation is a part of a finishing technique that aims to reduce the skin’s absorption ability to liquids, because in general the surface of the skin has high water absorption ability. The raw material for impregnation trial was 5 pieces of crust dyed cowhide with C and R qualities, thickness of 1.2-1.4 mm black. The impregnation material used in 2952 RE (acrylic polymer), melio resin A-716 (polyurethane resin), 8060 EE (penetrator) and aquades. Physical test results of tensile strength before repairing 17.01 N / mm2 after repairing 23.13 N / mm2, elongation of 70.73% after repairing 62.50%, and tear strength of 10.06N after repairing 25.17N. After improvement, there was an increase in the quality of skin quality according to SNI 06-4264-1996.